Dork diaries - RUSSELL, RACHEL RENEE (b)
Dork Diaries is a popular children's book series written in diary format by Rachel Renée Russell, following 14-year-old Nikki Maxwell as she navigates the horrors of middle school, popularity, crushes, and drama.
English